Sourpuss and Sweetie Pie - Juster, Norton, 1929-; Raschka, Christopher ([New York] : Scholastic, 2008)
Nanna and Poppy, who are expecting their granddaughter to visit, wonder whether Sweetie Pie or Sourpuss will show up, or if it may be both at the same time.
"Michael Di Capua books.".
Kirkus Review.
2.1
K-3
Keywords: Granddaughters -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Girls -- Fiction; Grandparent and child -- Fiction; Girls -- Fiction; Grandparent-grandchild relationship -- Fiction